Hippocampal differential expression underlying the neuroprotective effect of delta-9-tetrahydrocannabinol microdose on old mice - Guy Shapira; Guy Shapira; Ifat Israel-Elgali; Ifat Israel-Elgali; Meitar Grad; Eden Avnat; Lital Rachmany; Yosef Sarne; Noam Shomron; Noam Shomron; Noam Shomron (Frontiers in Neuroscience, 2023)
Delta-9-tetrahydrocannabinol (THC) is the primary psychoactive compound of the cannabis plant and an exogenous ligand of the endocannabinoid system. In previous studies, we demonstrated that a single microdose of THC (0.002 mg/kg, 3–4 orders of magnitude lower than the standard dose for rodents) exerts distinct, long-term neuroprotection in model mice subjected to acute neurological insults. When administered to old, healthy mice, the THC microdose induced remarkable long-lasting (weeks) improvement in a wide range of cognitive functions, including significant morphological and biochemical brain alterations. To elucidate the mechanisms underlying these effects, we analyzed the gene expression of hippocampal samples from the model mice. Samples taken 5 days after THC treatment showed significant differential expression of genes associated with neurogenesis and brain development. In samples taken 5 weeks after treatment, the transcriptional signature was shifted to that of neuronal differentiation and survival. This study demonstrated the use of hippocampal transcriptome profiling in uncovering the molecular basis of the atypical, anti-aging effects of THC microdose treatment in old mice.